Properties of Myofibrillar Protein in Frozen Pork Improved through pH-Shifting Treatments: The Impact of Magnetic Field - Bo Chen; Gaoang Du; Ke Li; Yu Wang; Panpan Shi; Junguang Li; Yanhong Bai (Foods, 2024)
The present study demonstrates the effects of pH-shifting treatments and magnetic field-assisted pH-shifting treatments on the properties of myofibrillar protein (MP) in frozen meat. The solubility results indicate that the pH-shifting treatments increased the solubility of MP from 16.8% to a maximum of 21.0% (pH 9). The values of surface hydrophobicity and protein particle size distribution indicate that the pH-shifting treatment effectively inhibited protein aggregation through electrostatic interactions. However, under higher pH conditions (pH 10, 11), the treatments assisted by the magnetic field increased the degree of aggregation. The total thiol content and SDS-PAGE results further suggest that the magnetic field-assisted pH-shifting treatment accelerated the formation of covalent bonds among MPs under the alkaline environment. The results of the Differential Scanning Calorimetry (DSC) and protein secondary structure analysis indicate that the magnetic field promoted the unfolding of protein structures in an alkaline environment, markedly reducing the effective pH levels of pH-shifting. Electron paramagnetic resonance (EPR) data indicate that the phenomenon might be associated with the increased concentration of free radicals caused by the magnetic field treatment. In summary, the application of magnetic field-assisted pH-shifting treatments could emerge as a potent and promising strategy to improve the protein properties in frozen meat.